Sensation seeking behaviours among adolescents in South-Eastern Nigeria secondary schools: need for counselling interventions (2019)
This study adopted descriptive survey design to investigate if there is a significant difference in the sensation seeking behaviours of secondary students based on gender, age range and body image. Simple random sampling technique was used to draw 1668 (male=838; female=830) with age range of 10 to 20 years and mean age of 15≥ from schools in South Eastern Nigeria. Brief Sensation Seeking Scale (r=.89) and Dresden Body Image Questionnaire (r=.87) were utilised to collect data. Three hypotheses were tested at 0.05 level of significance. Data was analyzed using Levenne’s test and Analysis of variance (ANOVA). The result shows that the male has higher sensation seeking behaviours (𝑥̅=77.244) than their female counterpart (x𝑥̅=76.119), however, this difference was not significant (t (1667) =.756 p > 0.5. p=.499). There was significant age difference in sensation seeking behaviours (F (4, 1664) = 7.574, P < 0.05). Respondents in age range of 10 to 12 years has highest mean score (x𝑥̅=74.244) while the least was those between ages 19 and above (x𝑥̅=65.331). There was significant difference (t (1667) = .517 p < 0.5) in sensation seeking behaviours of adolescents in south-eastern Nigeria based on perceived body image. The researcher concluded that the sensation seeking behaviours of students differs based on gender, age, and body image. Recommendations were made based on the outcome of the study.